The Effect of The Number of Tourists, Average Tourist Expenditure, And Original Local Government Revenue on The Economic Growth of Bali Province - Angella, Meicela Prasetya; M. Taufiq (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
The purpose of this study is to determine the influence of the number of tourists, average tourist expenditure, and Original Local Government Revenue on the economic growth of Bali Province. Tourism has rapidly developed over the past few decades. In Indonesia, tourism significantly contributes to the country's economic growth. Bali is one of the most popular tourist destinations in Indonesia. This study utilizes 12 years of time series data from 2010 to 2021 and is based on secondary data using quantitative methods and multiple linear regression with data processing conducted using SPSS software version 24. Based on the data analysis results, it can be concluded that the number of tourists has a positive and significant effect on the economic growth of Bali Province, the average tourist expenditure has a negative and insignificant effect on the economic growth of Bali Province, and Original Local Government Revenue has a negative and significant effect on the economic growth of Bali Province.